2012
DOI: 10.3139/146.110908
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution in pure aluminium processed by equal channel angular pressing at elevated temperature

Abstract: The potential for significant grain refinement in pure aluminium (99.9%) processed by means of equal channel angular pressing at 523 K (T/Tm ∼ 0.6) has been demonstrated. The mean grain size was significantly reduced from 1.2 mm to 4 µm after eight passes. The stored energy and high-angle grain boundary fraction increase until 6 passes and then remain almost constant until 8 passes. The grain refinement occurred in two stages, initially driven by the evolution of deformation inhomogeneties (deformation bands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Similar results have been reported by other authors [13,22]. Particularly interesting are the results of Subbarayan et al [20] on ECAPed pure Al at 250°C by route BC as the obtained mean grain size of 4µm after 8 passes. This difference of the average grain size was already explained by Mazurina et al [22] based on the effect of the dispersoids and precipitates delaying any strain relaxation within the grains.…”
Section: Microstructure Evolution After Different Ecap Passessupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results have been reported by other authors [13,22]. Particularly interesting are the results of Subbarayan et al [20] on ECAPed pure Al at 250°C by route BC as the obtained mean grain size of 4µm after 8 passes. This difference of the average grain size was already explained by Mazurina et al [22] based on the effect of the dispersoids and precipitates delaying any strain relaxation within the grains.…”
Section: Microstructure Evolution After Different Ecap Passessupporting
confidence: 89%
“…Accordingly, the transformation of LAGB into HAGB is controlled by the recovery rate. In this sense, if one compares the evolution of HAGBs of AA6082 with the results reported by Subbarayan et al [20] for pure Al ECAPed at 250 °C, it is revealed that the large Mg content in the present alloy must be behind the diminution of the recovery rate, [14].…”
Section: Microstructure Evolution After Different Ecap Passessupporting
confidence: 54%
“…Microstructure refinement to UFG level can be attained in a bulky metallic material by severe plastic deformation (SPD) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Therefore, the study of structure development during such thermomechanical processing is of particular significance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the major mechanism of strain-induced formation of new grains in aluminum alloys was the continuous dynamic recrystallization (cDRX) [8,12,14,26,28,30,31]. The structure evolution was characterized by the formation of deformation bands such as microshear bands (MSBs) at moderate strains, followed by their transformation to ultrafine grains with high-angle boundaries (HABs) at large strains [8,9,[12][13][14]23,28,30]. However, the particular structural mechanisms responsible for new grain formation during SPD are not clear yet and further studies are needed to reveal them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation